Destination-Oriented Route in Integrated LRT Web-Based System for Tourism - Sulong, Muhammad Suhaizan; Abdul-Aziz, Azlianor; Kamalrudin, Massila; Abdullah, Muhammad Haziq Lim; Abdullah, Fauziah (2007)
Light Rail Transit (LRT) Monorail and RapidKL are one of the major public transportations in Kuala Lumpur (KL), Malaysia and by traveling in LRT is said to be the most convenient public transport. In LRT RapidKL, there are three train-lines; Kelana Jaya Line, Ampang Line and Sri Petaling Line. This paper addresses the problem of selecting nearest destination station to a given places of interest such as shopping places, historical places and interesting places which may involve at least two LRT lines and need of interchange station. Thus, the traveler may face difficulty when they choosing incorrect station especially on different LRT lines which lead to time consuming and high cost. Producing web-based system for Internet applications in tourism has become wide spread and within this paper, the development of web-based application where destination-oriented routes need to be dynamically generated by determining the nearest station according to the specified places. In addition, this system provides detail information on interchange station (if any), estimated time arrive, total fares and operating hours.